Self-Efficacy and Emotions in Primary School Science Students During Online Research. an Exploratory Study in Chile; [Autoeficacia y Emociones del Estudiantado de Ciencias en la Enseñanza Básica Durante la Investigación en Línea. Un Estudio Exploratorio en Chile] - Joglar-Campos, C (GTE-Educational Technology Group, University of the Balearic Islands, 2023)
High perceived self-efficacy (PSE) and the feeling of positive emotions during the search for and management of information on the internet generate motivation in students and are relevant factors that have an impact on their academic performance. Therefore, this study aimed to identify, characterize, and analyze -by means of a Likert-like questionnaire- the PSE and the emotions mentioned by 334 fifth and sixth-grade students while performing tasks regarding the search and management of information on sciences. The students belonged to five vulnerable schools from the Santiago Metropolitan Region in Chile. Two response profiles were identified; 39% corresponds to profile 1 (low PSE and negative emotions) and 61% corresponds to profile 2 (high PSE and positive emotions). The characterization carried out indicates in the profiles that both the PSE and the emotions of students are in direct relationship with the school the student belonged to, and that fifth-grade students have a lower PSE than sixth graders. Schools whose students had a lower PSE also indicate negative emotions during the performing of the tasks, showing that emotional education and the teaching of digital skills contribute to deal with the completion of tasks in sciences and learning in better ways. © The Author(s) 2023.